Hubungan Antara Dukungan Sosial dan Religiusitas dengan Resiliensi Pada Penyintas Tsunami di Desa Way Muli Lampung Selatan - Purnama, Rahmad; Romlah, Listiyani Siti (Universitas Islam Negeri Raden Intan Lampung, 2021)
Resilience is an individual's ability to cope with and to face and be able to respond positively to unpleasant conditions. Individuals who have resilience in their lives are individuals who are able to survive in their life even though they are under stress, even in adversity or trauma that they have experienced in life. This study aims to determine the relationship between social support and religiosity with the resilience of tsunami survivors. The hypothesis put forward is that there is a positive relationship between social support and religiosity with the resilience of tsunami survivors. The subjects of this study were the people affected by the tsunami in Way Muli Village, South Lampung. The sample in this study was 50 people. The sampling technique used purposive random sampling. The research data were collected using a Resilience Scale. Social Support Scale. Religiosity Scale. The Resilience Scale consists of 36 valid items with a reliability coefficient of 0.920. The Social Support Scale consists of 43 valid items with a reliability coefficient of 0.936. The Religiosity scale consists of 26 valid items with a reliability coefficient of 0.928. Data analysis using multiple regression analysis techniques. The results obtained were Rx1.2y = 0.812 with a significant 0.000 (p <0.01). This means that there is a positive relationship between social support and religiosity with the resilience of tsunami survivors. The value of r2 = 0.659 means that in this study social support and religiosity only contributed 65.9% to resilience.